Cheap Labor and Southern Textiles, 1880-1930 - Wright, Gavin (Quarterly Journal of Economics, 1981)
An interpretation of the Southern capture of the American cotton textile market is presented, emphasizing capital accumulation and a process of "maturation" of the labor force. The market was divided along lines of product quality, and the precise rate of convergence was governed by the pace of demand. Simulations of the system uncover the surprising fact that the Great Textile Depression, which began in the 1920s, is not attributable to trends in demand, imports, or a chronic tendency to overproduce, but to the increase in real wages that occurred in the South as well as in the North. Possible interpretations of this development are discussed.